How to: design for inclusion. Perspectives and processes to address power inequities - Larson, A.M.; Sarmiento Barletti, J.P. (CIFOR-ICRAF, 2023)
MSPs have the potential to either challenge or reinforce existing power inequalities and experiences of exclusion. To enable inclusive dialogue and create more equitable patterns of stakeholder interaction, they need to be structured carefully, reflectively, and with an openness to adapt as goals/contexts/priorities change across time. For meaningful and effective participation, there are elements to consider that are internal to the MSP (getting people to the table) and elements that are external (engaging with the broader context of power relations you have just mapped).